Fire in the night - Byler, Linda (Byler, Linda. Lancaster burning, 2013)
The Amish community of Lancaster is being terrorized by barn fires. David and Malinda Beile''s barn was the first to go. The clues are sparse, but Levi, the Beilers' oldest son, happened to be awake in the middle of the night and spotted a white vehicle driving past the house with its lights off. Sarah, David and Malinda's daughter, is in her late teens and old enough to observe her parents' agony. Not only is she afraid, too, and wishing she could protect her parents, she's entranced by the flirtatious Matthew Stoltzfus. He's dating her friend, Rose, but when he tenderly bandages Sarah's hand after she burned it at the barn raising, she wonders who he is really interested in. When a second Amish barn burns for suspicious reasons, the Amish grow more restless. "We're too quiet too much of the time," a group of Amish men tell David Beiler, their minister. Seriously considering police protection, the increasingly tense community questions their traditional nonresistant approach to violence.